The Difference of Physiological and Proteomic Changes in Maize Leaves Adaptation to Drought, Heat, and Combined Both Stresses - Zhao, Feiyun; Zhang, Dayong; Zhao, Yulong; Wang, Wei; Yang, Hao; Tai, Fuju; Li, Chaohai; Hu, Xiuli (Frontiers in Plant Science, 2016)
After eight-leaf stage, maize is highly sensitive to drought, heat and their combination, which greatly affect its production. In present, it is still scare for analyzing maize response to combined drought and heat stress after eight-leaf stage. In this study, the content or activity of physical parameters such as H2O2, malondialdehyde (MDA), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR) was increased, but the quantum efficiency of photosystem II (ΦPSII) was decreased by drought, heat and their combination on eight-leaf stage. The most of increase or decrease was under combined stress conditions. Besides, to identify leaf proteins differentially regulated by three stresses on maize eight-leaf stage, proteomic analysis for maize leaves was performed by using multiplex iTRAQ-based quantitative proteomic and LC-MS/MS methods. Generally, the expression level of 135, 65 and 201 proteins was significantly changed under heat, drought and combined stress conditions, respectively. Among 135, 65 and 201 proteins, 61, 28 and 16 only responded to drought, heat and combined stress, respectively. The analysis indicated that chaperone proteins and proteases played important roles in maize adaptation to heat and combined stress, and that the leaf senescence promoted by ethylene-responsive protein and ripening-related protein might have active roles in maize tolerance to combined drought and heat stress.The signaling pathways related to the differently expressed proteins were clearly difference under three stress conditions. The functional characterization of these proteins will be helpful for discovering new targets to enhance maize tolerance to stress.